Pengaruh Growth, Profitability, Firm Size, Dan Capital Strucutre Terhadap Firm Value - Hendra Harischandra, Tony Sudirgo (Jurnal Paradigma Akuntansi, 2021)
This research aims to obtain empirical evidence the influence of growth, profitability, firm size, and capital structure to the firm value in the manufacturing company listed in the Indonesian Stock Exchange (IDX) during the year 2017-2019. This research uses secondary data obtain from the site www.idx.co.id. This research is conducted with a sample of 75 manufacturing company with data collection techniques is purposive sampling during a three-year period that is processed using Econometric Views (EViews) vers 10.0 program. This statistical method used to test the hypothesis is the multiple linear regression method. The results of this research show that Growth, Profitability and Capital Structure has effect on Firm Value, while Firm Size has no effect on Firm Value. The implication of this research is the need for the use of growth, profitability and capital structure to increase firm value and provide an overview of good decisions for investors.